Effects of geometrical parameter variations on the performance of silicon nitride-based optical microring resonators - Haroon, Hazura; Mohd Zain, Anis Suhaila; Idris, Siti Khadijah; Abdul Razak, Hanim; Othman, Maisara; Salehuddin, Fauziyah (National Institute of Optoelectronics, 2023)
This research proposes microring resonator (MRR) filter design based on silicon photonic technology on a silicon nitride (Si3N4) substrate for use as optical filters or passive wavelength filters in wavelength division multiplexing networks. Coupled mode theory and transfer matrix approaches were employed to investigate the effects of geometrical design variations on an optical filter model based on a Si3N4 MRR. Using MATLAB software, the geometrical parameters of a Si3N4 waveguide on silica were systematically analyzed and optimized. The four geometrical parameters studied to investigate changes in filter performance in terms of free spectral range and full wave half maximum were rib waveguide height, waveguide width, gap size, and ring radius. This work demonstrates the significance of selecting appropriate design parameters in the development of an optimal Si3N4-based MRR optical filter.